Un derecho europeo… ¿para qué contrato? Análisis sobre las fronteras del contrato en derecho comparado - Martin Oudin (Estudios de Deusto, 2012)
Studies are currently being carried out on the unification of contract law in Europe. Several texts have already been drafted and announce a possible future European contract code. Whatever the quality of these rules may be they will only be effective if their field of application is precisely defined, i.e. if European lawyers first agree on what a contract is. At the present time, national laws profoundly diverge on this point. An analysis of some of the main differences raises a number of questions concerning the classical view that a contract is an agreement giving rise to obligations between the contracting parties. Neither the principle of a reciprocal agreement nor the creation of obligations permit a clear distinction to be made between those situations that are contractual and those that are not. On the other hand, a definition based on the socio-economic function of contracts –production or, at least, anticipation– could bring together national conceptions of what constitutes a contract.